Functional variants at the 11q13 risk locus for breast cancer regulate cyclin D1 expression through long-range enhancers - French, J; Ghoussaini, M; Edwards, S; Meyer, K; Michailidou, K; Ahmed, S; Khan, S; Maranian, M; O'Reilly, M; Hillman, K; Betts, J; Carroll, T; et al. (2013)
Analysis of 4,405 variants in 89,050 European subjects from 41 case-control studies identified three independent association signals for estrogen-receptor-positive tumors at 11q13. The strongest signal maps to a transcriptional enhancer element in which the G allele of the best candidate causative variant rs554219 increases risk of breast cancer, reduces both binding of ELK4 transcription factor and luciferase activity in reporter assays, and may be associated with low cyclin D1 protein levels in tumors. Another candidate variant, rs78540526, lies in the same enhancer element. Risk association signal 2, rs75915166, creates a GATA3 binding site within a silencer element. Chromatin conformation studies demonstrate that these enhancer and silencer elements interact with each other and with their likely target gene, CCND1. © 2013 The American Society of Human Genetics.